Evaluasi dan Hubungan Ketepatan Penggunaan Obat Anti Tuberkulosis Lini 1 terhadap Karakteristik Pasien Rawat Jalan di Rumah Sakit Umum Daerah X: Evaluation and Correlation of the Appropriateness of the Use of First-Line Anti-Tuberculosis Drugs to the Characteristics of Outpatients at X Regional General Hospital - Musdar, Tamzil Azizi; Hasmar, Wahyu Nuraini; Azis, Muhammad Israwan; Zuchrullah, Mukhtasyam; Saputro, Syaifullah; Kurniati, Kurniati; Ihsan, Mifta Khaerati; Supardi, Nurjannah; Santi, Elvira; Asjur, Asti Vebriyanti (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2025)
Tuberculosis is an infectious disease that attacks the respiratory organs (lungs). This study aims to determine the characteristics of the use of first-line anti-tuberculosis drugs (OAT) and evaluate the use of OAT based on the 2019 Tuberculosis Management Guidelines and analysis of the relationship between patient characteristics and treatment outcomes. Data collection was retrospective, with a sample size of 91 Patient Medical Records. The results showed that the most common patient characteristics were male (57.1%), age 46-55 years (24.2%), weight 38-54 kg (53.8%), with working status (52.7%), without comorbidities (89%), new patient type (92.3%), type of OAT category 1 (100%), unsuccessful treatment results (54.9%). Evaluation of OAT use was 100% correct indication, correct patient, and correct drug. While the correct dose (97.8%), correct duration of treatment (41.8%). The relationship analysis obtained age factors (p = 0.04), duration of treatment (p = 0.001) have a significant relationship to treatment outcomes, while gender (p = 0.301) and the number of P.PK (p = 0.733) both do not have a significant relationship to treatment outcomes. Keywords: TB, Evaluation of OAT Use, X Hospital Abstrak Penyakit Tuberculosis merupakan penyakit infeksi menular yang menyerang organ pernafasan (paru-paru). Penelitian ini bertujuan untuk mengetahui karakteristik penggunaan obat anti tuberkulosis (OAT) lini 1 dan mengevaluasi penggunaan OAT berdasarkan Pedoman Tatalaksana Tuberkulosis tahun 2019 serta analisis hubungan antara karakteristik pasien terhadap hasil pengobatan. Pengumpulan data secara retrospektif, jumlah sampel sebanyak 91 Rekam Medik Pasien. Hasil penelitian menunjukkan karakteristik pasien terbanyak yaitu berjenis kelamin laki-laki (57,1%), usia 46-55 tahun (24,2%), berat badan 38-54 kg (53,8%), dengan status bekerja (52,7%), tanpa penyakit penyerta penyerta (89%), tipe pasien baru (92,3%), jenis OAT kategori 1 (100%), hasil pengobatan tidak berhasil (54,9%). Evaluasi penggunaan OAT 100 % tepat indikasi, tepat pasien, dan tepat obat. Sedangkan tepat dosis (97,8%), tepat lama pengobatan (41,8%). Analisis hubungan diperoleh faktor usia (p=0,04), lama pengobatan (p=0,001) memiliki hubungan yang signifikan terhadap hasil pengobatan, sedangkan jenis kelamin (p=0,301) dan banyaknya penyakit penyerta kronis (P.PK) (p=0,733) keduanya tidak memiliki hubungan signifikan terhadap hasil pengobatan. Kata Kunci: TBC, Evaluasi Penggunaan OAT, RSUD X